Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/jm2007613
|View full text |Cite
|
Sign up to set email alerts
|

Structure Based Drug Design of Crizotinib (PF-02341066), a Potent and Selective Dual Inhibitor of Mesenchymal–Epithelial Transition Factor (c-MET) Kinase and Anaplastic Lymphoma Kinase (ALK)

Abstract: Because of the critical roles of aberrant signaling in cancer, both c-MET and ALK receptor tyrosine kinases are attractive oncology targets for therapeutic intervention. The cocrystal structure of 3 (PHA-665752), bound to c-MET kinase domain, revealed a novel ATP site environment, which served as the target to guide parallel, multiattribute drug design. A novel 2-amino-5-aryl-3-benzyloxypyridine series was created to more effectively make the key interactions achieved with 3. In the novel series, the 2-aminopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
580
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 799 publications
(590 citation statements)
references
References 57 publications
(61 reference statements)
8
580
0
2
Order By: Relevance
“…The most notable is Gleevec (imatinib), which is a type II kinase inhibitor targeting the DFG-out conformation of its targets c-Abl and c-kit (64). Crizotinib itself does this in its complex with c-Met, the kinase toward which it was initially targeted, by interacting with Tyr 1230 on a unique, inactive conformation of the A-loop (19). Perturbations to the wild-type, inactive ALK kinase domain structure do occur and alternative conformations can be trapped by small molecule inhibitors as we have shown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most notable is Gleevec (imatinib), which is a type II kinase inhibitor targeting the DFG-out conformation of its targets c-Abl and c-kit (64). Crizotinib itself does this in its complex with c-Met, the kinase toward which it was initially targeted, by interacting with Tyr 1230 on a unique, inactive conformation of the A-loop (19). Perturbations to the wild-type, inactive ALK kinase domain structure do occur and alternative conformations can be trapped by small molecule inhibitors as we have shown.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of these investigations, we sought to understand the structural basis for activation of ALK by the two most common neuroblastoma mutants, F1174L and R1275Q. We report here crystal structures of both mutants and we use the published structure of the ALK-crizotinib complex to show that these mutants produce no steric impediment to crizotinib binding (19). In addition, during the course of our medicinal chemistry efforts two other classes of ALK inhibitors were identified that stabilized the ALK A-loop in previously unobserved conformations.…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is an oral small-molecule tyrosine kinase inhibitor, originally developed as a c-MET inhibitor and later found an inhibitor for ALK phosphorylation [30,31]. In vitro studies demonstrated that crizotinib is potent in neuroblastoma cell lines with ALK amplification or the R1275Q mutation, one of the most common ALK variants in neuroblastoma [32].…”
Section: Alk Targeted Agents In Neuroblastomamentioning
confidence: 99%